Faktor Risiko Kesehatan Lingkungan Di Sekolah Dasar Kabupaten Padang Pariaman - Miladil Fitra; Awaluddin Awaluddin; Alsri Windra Doni; Dismo Katiandagho (POLTEKKES KEMENKES MANADO, 2020)
School conditions that do not meet environmental health requirements are a threat to students and school members to be affected by health problems and infectious diseases. The purpose of this study was to analyze risk factors for environmental health at SDN 13 Batang Gasan and the potential health problems that would arise. This research is descriptive, with the population is the facilities and infrastructure and all students of SD Negeri 13 Batang Gasan, totaling 82 people. Data analysis was performed using environmental health risk factor analysis, namely providing answers about the risks that will arise, by dividing 6 risk criteria, namely very high (> 80%), high (60% -79%), moderate (40% -59%), low (20% -39%), very low (1% -19%) and safe / not risky (0%). The results of the study prove that the level of environmental health risk in Public Elementary School 13 is high (65%). It is suggested that schools need to make efforts to control risk factors.